2022
DOI: 10.3389/fncel.2022.914985
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoreceptor Piezo1 Is Downregulated in Multiple Sclerosis Brain and Is Involved in the Maturation and Migration of Oligodendrocytes in vitro

Abstract: Mechanical properties of the brain such as intracranial pressure or stiffness of the matrix play an important role in the brain’s normal physiology and pathophysiology. The physical properties are sensed by the cells through mechanoreceptors and translated into ion currents which activate multiple biochemical cascades allowing the cells to adapt and respond to changes in their microenvironment. Piezo1 is one of the first identified mechanoreceptors. It modulates various central nervous system functions such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Whether acidic pH indeed inhibits oligodendrocyte maturation and/or maintains OPCs in an undifferentiated state (PDGFRα expression), and whether TDAG8 is involved in these processes needs to be investigated further. Low pH could act on other receptors that have been shown to regulate OPC differentiation and migration, such as EBI2 or the mechanosensing ion channel Piezo1, which is inhibited in pH under 6.9 [29,38,43,44]. Nevertheless, looking at myelination in vivo in untreated TDAG8 KO mice, our explorations demonstrate that TDAG8-mediated signalling is not required for normal myelination in the mouse CNS.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Whether acidic pH indeed inhibits oligodendrocyte maturation and/or maintains OPCs in an undifferentiated state (PDGFRα expression), and whether TDAG8 is involved in these processes needs to be investigated further. Low pH could act on other receptors that have been shown to regulate OPC differentiation and migration, such as EBI2 or the mechanosensing ion channel Piezo1, which is inhibited in pH under 6.9 [29,38,43,44]. Nevertheless, looking at myelination in vivo in untreated TDAG8 KO mice, our explorations demonstrate that TDAG8-mediated signalling is not required for normal myelination in the mouse CNS.…”
Section: Discussionmentioning
confidence: 89%
“…Our explorations culminated in experiments using human material from MS patients where we found that TDAG8 is upregulated in MS plaques. Differentiation of the MO3.13 oligodendrocytes in vitro can be achieved by stimulation with either PMA or by culturing in SFM [37,38]. The cell maturation is indicated by reduced expression of the OPC or pre-oligodendrocyte markers and an increase in mature and myelinating oligodendrocyte markers [29,39].…”
Section: Discussionmentioning
confidence: 99%
“…In the oligodendrocyte lineage cells, Piezo1 is highly expressed in OPCs, where its activation decreases both proliferation and migration. 166,189 The transcriptional coactivators YAP and TAZ with the PDZ domain encoded by the gene WWTR1 are part of the Hippo (named after the Hpo/MTS1/2 kinase) pathway cascade, which regulates organ size by modulating cell proliferation and apoptosis (Figure 3). In the unphosphorylated state, the coactivators YAP and TAZ are nuclear and favor proliferation due to the transcription of cell cycle genes.…”
Section: Mechanotransduction In Response To Tension: Piezo1 Yap and R...mentioning
confidence: 99%
“…It is expressed in neurons, astrocytes, and microglial cells at low levels. In the oligodendrocyte lineage cells, Piezo1 is highly expressed in OPCs, where its activation decreases both proliferation and migration 166,189 …”
Section: Mechanotransduction Allows Chromatin and Nuclear Lamina To A...mentioning
confidence: 99%
“…A role of Piezo1 in cellular migration has been explored in different contexts, viz. cancer cells, fibroblasts, mesenchymal stem cells, keratinocytes, oligodendrocytes and macrophages, which show differential involvement of Piezo1 depending on contexts (Hung et al, 2016; Chubinskiy Nadezhdin et al, 2019; Mousawi et al; 2020, Wang et al, 2021; Gao et al, 2021; Holt et al, 2021; He Y et al, 2022; Velasco-Estevez et al, 2022). The previous studies point to the possibility of a role of Piezo1 in confinement sensing and integrin activation in moving cells, while it deters integrin-independent cell motility, usually referred to as amoeboid movement (McHugh et al, 2010; Hung et al, 2016).…”
Section: Introductionmentioning
confidence: 99%